A Prospective Randomized Comparison of Postoperative Pain and Complications after Thyroidectomy under Different Anesthetic Techniques: Volatile Anesthesia versus Total Intravenous Anesthesia - Jun-Young Jo; Yeon Ju Kim; Seong-Soo Choi; Jihoon Park; Han Park; Kyung-Don Hahm (Pain Research and Management)
While the postoperative outcome is favorable, post-thyroidectomy pain is considerable. Reducing the postoperative acute pain, therefore, is considered important. This study investigated whether the pain intensity and need for rescue analgesics during the immediate postoperative period after thyroidectomy differ according to the methods of anesthesia. Seventy-two patients undergoing total thyroidectomy under general anesthesia were examined. Patients were randomly assigned to undergo either total intravenous anesthesia with remifentanil and propofol (TIVA, n = 35) or propofol induction and maintenance with desflurane and nitrous oxide (volatile anesthesia [VA], n = 37). The mean administered dose of remifentanil was 1977.7 ± 722.5 μg in the TIVA group, which was approximately 0.268 ± 0.118 μg/min/kg during surgery. Pain scores based on a numeric rating scale (NRS) and the need for rescue analgesics were compared between groups at the postoperative anesthetic care unit (PACU). The immediate postoperative NRS values of the TIVA and VA groups were 5.7 ± 1.7 and 4.7 ± 2.3, respectively (P = 0.034). Postoperative morphine equianalgesic doses in the PACU were higher in the TIVA group than in the VA group (16.7 ± 3.8 mg vs. 14.1 ± 5.9 mg, P = 0.027). The incidence of immediate postanesthetic complications did not differ significantly between groups. In conclusion, more rescue analgesics were required in the TIVA group than in the VA group to adequately manage postoperative pain while staying in the PACU after thyroidectomy.